2009
DOI: 10.1111/j.1365-2249.2008.03865.x
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation in the human genome and its implication in autoimmunity

Abstract: SummaryThe causes of autoimmune disease remain poorly defined. However, it is known that genetic factors contribute to disease susceptibility. Hitherto, studies have focused upon single nucleotide polymorphisms as both tools for mapping and as probable causal variants. Recent studies, using genome-wide analytical techniques, have revealed that, in the genome, segments of DNA ranging in size from kilobases to megabases can vary in copy number. These changes of DNA copy number represent an important element of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 50 publications
1
48
0
Order By: Relevance
“…However, recently it has been shown that copy number variants (CNVs) are also associated with complex diseases, including autoimmune diseases [reviewed in Ref. (10)]. CNVs are large DNA segments, ranging from kilobases to megabases, that are altered within the genome as a result of duplications, deletions, insertions, inversions, or complex combinations of rearrangements [reviewed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently it has been shown that copy number variants (CNVs) are also associated with complex diseases, including autoimmune diseases [reviewed in Ref. (10)]. CNVs are large DNA segments, ranging from kilobases to megabases, that are altered within the genome as a result of duplications, deletions, insertions, inversions, or complex combinations of rearrangements [reviewed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the immunity genes that show CNV have been investigated in the context of susceptibility 347 to autoimmune diseases (Olsson and Holmdahl 2012;Schaschl et al 2009). Perhaps the best-348 established is the CNV of complement C4 within the MHC region at chromosome 6p21.32.…”
Section: Host Cnv and Autoimmune Disease 346mentioning
confidence: 99%
“…The observed differences in FCGR1A expression could be due to variation in for instance a regulatory region; it is also possible that our marker is linked with a copy number variant of the FCGR1A gene (Hindorff et al 2009). In humans, there is a segmental duplication region on chromosome 1q23 which encompasses several low-affinity Fc gamma receptors, e.g., FCGR2A, FCGR2B, and FCGR3A (Schaschl et al 2009). This locus is located about 10 Mb from the human FCGR1A gene.…”
Section: Disscussionmentioning
confidence: 99%